1985
DOI: 10.1002/ana.410180111
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside patterns in amyotrophic lateral sclerosis brain regions

Abstract: In a search for evidence of biochemical disorders in regions of postmortem brain other than the motor cortex in amyotrophic lateral sclerosis (ALS), ganglioside patterns were also examined in the frontal, temporal, and parahippocampal gyrus cortex. In 21 ALS brains studied (20 sporadic, 1 familial), abnormal patterns were found in the frontal cortex (81%), temporal cortex (75%), motor cortex (70%), and parahippocampal gyrus cortex (71%). Patterns were established by measuring the percentage distribution of 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…A recent metabolic study by means of PET [9] showed diffuse cerebral cortical hypometabolism, suggesting extramotor neuronal func tional impairment. Studies of ganglioside pattern abnor malities also showed that the disease process in ALS extends beyond the motor cortex [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent metabolic study by means of PET [9] showed diffuse cerebral cortical hypometabolism, suggesting extramotor neuronal func tional impairment. Studies of ganglioside pattern abnor malities also showed that the disease process in ALS extends beyond the motor cortex [12].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of motor neuron disease (MND) as a dis order restricted to the motoneurons has been challenged on the basis of electrophysiological or pathological evi dence of changes in central and peripheral sensory fibers [1][2][3][4] and pathological [5][6][7][8], neuroradiological [9][10][11] and biochemical [12] verification of extramotor cerebral involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence includes the detection of unique gangliosides (10), high titer serum auto-antibodies to GM2 and GM1 (11,12), and elevated GM2 levels within the motor cortex of ALS patients (13). Furthermore, a number of neuromuscular diseases are associated with mutations in genes that regulate the metabolism of Cer and GSLs.…”
mentioning
confidence: 99%
“…There is, however, considerable discrepancy between clinical signs and extent and degree of pathological involvement [lo, 12, 21, 22, 291. This is especially noticeable in the motor and associated motor cortex where histological changes may be unremarkable, even in the presence of clinically severe UMN involvement [G, 10,11,25,291. In addition, it is not certain whether atrophy precedes loss in affected neurons.…”
mentioning
confidence: 99%